EL ESTILO COGNITIVO Y SU INFLUENCIA EN LA SOLUCIÓN DE PROBLEMAS EN QUIMICA. Un estudio en el aula de clase - Sandoval Q., Myriam Esperanza; Caicedo López, Humberto (Tecné, Episteme y Didaxis: TED, 2000)
The experimental study was made to get additional empirical evidence to show how the cognitive style in its field dependence-independence dimension differentiate students with different aptitude to solve chemistry problems. Twenty eight students participated, 11 female and 17 male, average age seventeen. The test used was a set of simple problems, to obtain information about level of perception and selected strategy to get an appropriate solution.